A Prediction Formula for The Estimation of Sediment Load in The Upper Reach of Al-Gharraf River (Journal of Engineering, 2021)
The presence of deposition in the river decreases the river flow capability's efficiency due to the absence of maintenance along the river. In This research, a new formula to evaluate the sediment capacity in the upstream part of Al-Gharraf River will be developed. The current study reach lies in Wasit province with a distance equal to 58 km. The selected reach of the river was divided into thirteen stations. At each station, the suspended load and the bedload were collected from the river during a sampling period extended from February 2019 till July 2019. The samples were examined in the laboratory with a different set of sample tests. The formula was developed using data of ten stations, and the other three stations were used for validation. The determination coefficient, root mean square error and average relative error values were equal to 0.987,0.97 kg/s and 7%, respectively. Also, the values of the sediment load that resulted from the formula close to the results of the HEC-RAS model from a previous study, and the determination coefficient, root mean square error, and average relative error values were equal to  0.988, 0.88 kg/s, and 7 %  respectively for the simulated model.